2009
DOI: 10.1159/000228935
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Arteriograph – A New Oscillometric Device to Measure Arterial Stiffness in Patients on Maintenance Hemodialysis

Abstract: Background: Measuring arterial stiffness (augmentation index (AI), aortic pulse wave velocity (PWV)) in hemodialysis (HD) patients has prognostic significance. To assess its validity, the new oscillometric Arteriograph device (AIA, PWVA) was compared to the validated PulsePen tonometer (AIP, PWVP). Methods: AI and PWV were measured in 98 patients with both devices before HD. Validity was evaluated by Pearson’s correlation, Bland-Altman analysis, and by assessing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 39 publications
1
22
1
2
Order By: Relevance
“…[23][24][25] Survival studies in adults indicate that PWV measured by applanation tonometry has a good clinical predictive value. 20 Involving more than 1000 children, our research group has furthermore confirmed the applicability of the PP device to mass screening of children of different age groups. 10 The method proved to be fairly reproducible and provided reference values for PWV in children and teenagers.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…[23][24][25] Survival studies in adults indicate that PWV measured by applanation tonometry has a good clinical predictive value. 20 Involving more than 1000 children, our research group has furthermore confirmed the applicability of the PP device to mass screening of children of different age groups. 10 The method proved to be fairly reproducible and provided reference values for PWV in children and teenagers.…”
Section: Discussionmentioning
confidence: 53%
“…10 A multitude of various methods and techniques have been used to assess PWV in adults such as applanation tonometry, 11,12 ultrasound, 13,14 methods using mechanotransducers 15 and computerized oscillometry; 16 furthermore, a number of comparative studies with diverging results have been published concerning the comparability of the different methods. [17][18][19][20][21] Instruments based on the principle of applanation tonometry (PulsePen (PP) (DiaTecne, Milan, Italy) and Sphygmocor (SC) (AtCor, Sydney, Australia) have been extensively used. They are easily applied in adults and children and have a fair reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…Although new methods to assess PWA have been partially validated, [18][19][20][21] non-invasive assessment of aortic wave reflection characteristics is normally performed via applanation tonometry. High-fidelity radial artery pressure waveforms are recorded using a 'pencil type' micromanometer (Millar Instruments, Houston, TX, USA).…”
Section: Pulse Wave Analysismentioning
confidence: 99%
“…Although new methods to assess PWV have been partially validated, the gold standard method of non-invasive assessment of PWV continues to be applanation tonometry. 5,10,14,16,[18][19][20][21] In general, pressure waveforms are gated with simultaneous electrocardiographs and are used to calculate the PWV between the two sites (carotidfemoral). Foot-to-foot PWV is calculated by determining the delay between the appearance of the pressure waveform foot in the carotid and femoral sites (Dt).…”
Section: Pulse Wave Analysismentioning
confidence: 99%
See 1 more Smart Citation